Agir, aprender, formar, intervir, agir uma experiência dos consultores internos na gestão do conhecimento da Petrobrás UN-RNCE - Freitag, Maria Salete Batista (2008)
This research aims at studying the formation of internal consultants in organizational setting in the joint resolution of problems, around the conversion of knowledge. The objective of research is to understand and explain the meanings attributed by Petrobras internal consultants to their practice and training for the conversion process of tacit knowledge into explicit, around the joint resolution of their problems with their collaborators. It has directed the next question: what the meanings assigned by the consultants of Unidade de Negócios Rio Grande do Norte e Ceara (UN-RNCE) in Knowledge Management (KM), for their interventionist and formative practices in problem solving, as well as conversion of tacit knowledge in explicit? This paper has assumed that there is a dual logic integrated into its daily practices: solving troubles and converting knowledge. The thesis has considered the daily practices of these consultants are characterized as epistemic spaces and permanent education through the conversion of knowledge. It has adopted the principles of multi-referential approach as foundations, regarding the translation of a variety of angles, perspectives and prospects which allow the interpretation and understanding of complex issues that are part of conversion of knowledge. The understanding and explanation of the senses are based on the methodology of the comprehensive interview; taking ownership is the sensitive listening for comprehensive interpretation of oral discourses of ten consultants, in addition to the autoscopy that putting into practice, thus, the stance of the researcher as an intellectual craftsman. Furthermore, it has assessed that the limits and possibilities for training and learning in the conversion of knowledge arise, on one hand from a predominantly driven training culture by the paradigm of technical rationality and one the other hand, from a set of relationship to knowledge and relation to know , revealed in the search for training in other dimensions. There are tensions between the local and global demands located in a situation marked by a systemic organization of knowledge. However, the context is perceived by researchers as impregnated by the discontinuity, unpredictability and uncertainty; mobilizing a number of elements necessary for the mediation in training practices of these consultants. Finally, it has set an instrumental and technological support, restricting the formation and undermining the position of the consultancy as nuclear function in Knowledge Management